Exploring Social Identities in Indonesia: The Role of Religious and Ethnic Identities in Evaluating Well-Being - Tery Setiawan; Missiliana Riasnugrahani; Ellen Theresia; Meta Dwijayanthy; Marissa Chitra Sulastra (Changing Societies & Personalities)
This study examines the role of religious and ethnic identities on individuals’ reported relational well-being (RWB) in Indonesia. Our findings reveal that religious identity significantly impacts life evaluations, with active engagement in religious practices positively correlating with RWB. Conversely, ethnic identity does not demonstrate a significant association with RWB, particularly among younger adults, suggesting that positive religious relationships may supersede ethnic affiliations in well-being assessments. Notably, while particularistic and religiocentrism beliefs do not correlate with RWB, the salience of religious values, such as the principle of treating others as one wishes to be treated, exhibits a positive relationship with life evaluations. This underscores the importance of religious identity over ethnic identity in shaping well-being. The study contributes valuable insights for scholars and policymakers aiming to foster intergroup harmony and enhance life satisfaction through social identity interventions.